Removal of Bromine from the non-metallic fraction in printed circuit board via its Co-pyrolysis with alumina. (1st January 2022) - Ali, Labeeb; A.Mousa, Hussein; Al-Harahsheh, Mohammad; Al-Zuhair, Sulaiman; Abu-Jdayil, Basim; Al-Marzouqi, Mohamed; Altarawneh, Mohammednoor
Graphical abstract: Highlights: Co-pyrolysis of PCBs and alumina is investigated herein. De-bromination of alumina is observed using various techniques. DFT calculations establish governing reaction mechanism for HBr uptake. Kinetic parameters are acquired for PCBs-alumina composites. Abstract: The effectiveness of a recycling approach of the printed circuit board (PCBs), and, thus, the quality of polymeric constituents, primarily rests on the capacity to eliminate the bromine content (mainly as HBr). HBr is emitted in appreciable quantities during thermal decomposition of PCB-contained brominated flame retardants (BFRs). The highly corrosive, yet relatively reactive HBr, renders recovery of bromine-free hydrocarbons streams from brominated polymers in PCBs very challenging. Via combined experimental and theoretical frameworks, this study explores the potential of deploying alumina (Al2 O3 ) as a debromination agent of Br-containing hydrocarbon fractions in PCBs. A consensus from a wide array of characterization techniques utilized herein (ICP-OES, IC, XRD, FTIR, SEM-EDX, and TGA) clearly demonstrates the transformation of alumina upon its co-pyrolysis with the non-metallic fractions of PCBs, into aluminum bromides and oxy-bromides. ICP-OES measurements disclose the presence of high concentration of Cu in the non-metallic fraction of PCB, along with minor levels of selected valuable metals. Likewise, elemental ionic analysis by IC demonstrates an elevated concentration of bromine in washed alumina-PCBs pyrolysates, especially at 500 °C. The Coats-Redfern model facilitates the derivation of thermo-kinetic parameters underpinning the thermal degradation of alumina-PCB mixtures. Density functional theory calculations (DFT) establish an accessible reaction pathway for the HBr uptake by the alumina surface, thus elucidating chemical reactions governing the observed alumina debromination activity. Findings from this study illustrate the capacity of alumina as a HBr fixation agent during the thermal treatment of e-waste.